Advances in Optical Aptasensors for Early Detection and Diagnosis of Various Cancer Types - Zahra, Qurat ul ain; Khan, Qaiser Ali; Luo, Zhaofeng (Frontiers in Oncology, 2021)
Cancer is one of the life-threatening concerns worldwide. Sensitive and early-stage diagnostics of different cancer types can make it possible for the patients to get through the best available treatment options to combat this menace. Among several new detection methods, aptamer-based biosensors (aptasensors) have recently shown promising results in terms of sensitivity, identification, or detection of either cancerous cells or the associated biomarkers. In this mini-review, we have summarized the most recent (2016-2020) developments in different approaches belong to optical aptasensor technologies being widely employed for their simple operation, sensitivity, and early cancer diagnostics. Finally, we shed some light on limitations, advantages, current challenges of aptasensors in clinical diagnostics, and elaborated on some future perspectives.